Misdiagnosis of Bipolar Disorder: Rare or Frequent? - Sevda Korkmaz; Murad Atmaca; Gülay Taşcı; Şuheda Kaya (Genel Tıp Dergisi)
Background: As much there have been limited number of studies which have examined misdiagnosis of bipolar disorder, it is so difficult to say that there are enough systematic research to identify the diagnostic rate of bipolar disorder. On the other hand, we did not find any research in Turkey. For this reason, we wondered what is situation in our country in terms of misdiagnosis of bipolar disorder. Methods: The present study was done at xxx University, School of Medicine, Department of Psychiatry. Patients who were from both out-patient and in-patient clinics were included in the study. After a selection process, 171 patients with bipolar disorder were enrolled. In this group of patients, misdiagnosis of bipolar disorder were investigated. Results: 56.14 percent of patients had misdiagnosis of bipolar disorder. The most frequent misdiagnosis was fetermined to be major depressive disorder (in fifty cases, 54.3%). Followings were schizoaffective disorder (in eighteen cases, 24.3%), schizophrenia (in thirteen patients, 24.3%), delusional disorder (in thirteen patients, 24.3%), dysthymic disorder (in ten cases, 15.9%), generalized anxiety disorder ((in ten cases, 15.9%), obsessive compulsive disorder (in seven cases, 12.6%), paranoid personality disorder (in two cases, 4.1%). Conclusions: The results of the study suggest that bipolar disorder is frequently misdiagnosed one and that the most frequent misdagnoses were majör depressive disorder and following psychotic spectrum disorders. Clinicians should be aware of frequent misdiagnosis in patients with bipolar disorder.